The Mystification of Genetically Modified Food Nourishing the Faith, Feeding the Tummy - Risyawati Mohamed Ismail (International Review of Management and Marketing, 2016)
In questioning the emphasized on Genetically Modified Food (GMF), one should consider the importance of biotechnology to food production in Malaysia. Under the 9th Malaysia Plan more than RM 20000 million was allocated for the biotechnology sector in order to ensure that the agriculture sector in Malaysia, relating to food production and processing will improve significantly through advance biotechnology process. However, in regards to Muslim consumerism there are general concerns on whether or not GMF is halal. Such crucial issue of GMF has become a problem especially for religious and governing authorities whom protect the halal aspect of Muslim consumerism. GMF even if found to be permissible from the Islamic perspective, the question remains on the toyibban criterion of Muslim dietary requirement which emphasized that food must be safe, nutritious and healthy for consumption.  This paper is a conceptual paper based on an extensive review of current and available literatures,  on the subject of GMF, focusing on halal consumerism.